Focal polymicrogyria in children: Contribution of invasive explorations and epileptogenicity mapping in the surgical decision. (March 2021) - Sculier, Claudine; Taussig, Delphine; David, Olivier; Blustajn, Jerry; Ayoubian, Leila; Bonheur, Julie; Bulteau, Christine; Chipaux, Mathilde; Dorison, Nathalie; Raffo, Emmanuel; Ferrand-Sorbets, Sarah; Dorfmüller, Georg; et al.
Highlights: PMG, although the most common epileptogenic brain malformation, represents only a small percentage of the patients operated on for epilepsy. In focal PMG there is little concordance between the lesion and the EZ frequently requiring the use of invasive explorations. Epileptogenic mapping helps to refine the identification of the epileptogenic zones. Due to the frequent involvement of the motor cortex within the PMG surgical possibilities are limited. Abstract: Objective: Report of the contribution of invasive EEG (iEEG) and epileptogenicity mappings (EM) in a pediatric cohort of patients with epilepsy associated with focal polymicrogyria (PMG) and candidates for resective surgery. Method: Retrospective pediatric case series of patients presenting focal PMG-related refractory epilepsy undergoing an invasive exploration (iEEG) at Fondation Rothschild Hospital. We reviewed clinical data, structural MRI, and visual analysis of iEEG recordings. Moreover, time-frequency analysis of SEEG signals with a neuroimaging approach (epileptogenicity maps) was used to support visual analysis. Results: Between 2012 and 2019, eight patients were selected. Five patients were explored with stereoelectroencephalography (SEEG) only, one patient with subdural exploration (SDE) only and two patients first underwent SEEG and then SDE. The mean age at seizure onset was 40.3 months (range 3–120), and the mean age for the iEEG 10.8 years (range 7–15). The epileptogenic zone (EZ) appeared concordant to the PMG lesion in only one case, was larger in three cases, smaller in two cases and different in one case. Four cases were selected for tailored resective surgery and one for total callosotomy. Two patients remained seizure-free at their last follow-up (mean 32.6 months, range 7–98). Epileptogenicity mapping (EM) refined the qualitative analysis, showing in four patients an EZ larger than visually defined. Conclusion: This study is the first pediatric study to analyze the value of iEEG and EM as well as operability in focal PMG-related refractory epilepsy. The results illustrate the complexity of this pathology with variable concordance between the EZ and the lesion and mixed response to surgery.